Frontopolar tDCS Induces Frequency-Dependent Changes of Spontaneous Low-Frequency Fluctuations: A Resting-State fMRI Study. (17th December 2021) - Ren, Ping; Ma, Manxiu; Wu, Donghui; Ma, Yuanye
Abstract: Transcranial direct current stimulation (tDCS) is a noninvasive neuromodulation technique that can modulate cortical excitability and behavioral performance. However, its effects on spontaneous low-frequency fluctuations of brain activity are still poorly understood. Here, we systematically investigated the frontopolar tDCS effects on resting-state brain activity and connectivity. Twelve healthy participants were recruited and received anode, cathode, and sham stimulation in a randomized order. Resting-state functional magnetic resonance imaging was performed before and after stimulation. Functional connectivity was calculated to examine tDCS effects within and beyond the frontopolar network. To assess the frequency-dependent changes of brain activity, fractional amplitude of low-frequency fluctuations (fALFF) was computed in the slow-4 (0.027–0.073 Hz) and slow-5 (0.01–0.027 Hz) bands. The results showed anodal tDCS-induced widespread connectivity reduction within and beyond the frontopolar network. Regardless of tDCS polarity, stimulation effect on fALFF was significantly larger in slow-5 band compared with the slow-4. Notably, anodal tDCS-induced connectivity changes were associated with pre-tDCS fALFF in slow-4 band, showing positive correlations in the frontal regions and negative correlations in the temporal regions. Our findings imply that tDCS-induced brain alterations may be frequency-dependent, and pre-tDCS regional brain activity could be used to predict post-tDCS connectivity changes.